2022
DOI: 10.1097/mao.0000000000003720
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Surgical Approaches for Acoustic Neuroma Resection: Do Patients Perceive a Difference in Quality-of-Life Outcomes?

Abstract: Objective: The objective of this study is to further patient-physician discussion regarding postoperative quality of life expectations after surgical acoustic neuroma resection. Study Design: This study is retrospective prospective. Qualifying patients were identified and administered Penn Acoustic Neuroma Quality-of-Life (PANQOL) Scale. Setting: The setting was Loyola University Chicago Health System. Patients: Three hundred twenty-six patients at our center with surgically resected acoustic neuroma between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 10 Our previous study looking specifically at surgical approach and PANQOL scores showed that patients who had the retrosigmoid approach have higher PANQOL scores than those who underwent the translabyrinthine approach. 29 The two senior authors (DEA and JPL) aim for GTR while recognizing that a small amount of residual tumor as a means of functional preservation is acceptable. Inclusion of various tumor sizes in this analysis highlights a potential difference in expectations between patients with small and large tumors; patients with larger tumors have a trend towards reporting improved PANQOL health and face scores, although these were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Our previous study looking specifically at surgical approach and PANQOL scores showed that patients who had the retrosigmoid approach have higher PANQOL scores than those who underwent the translabyrinthine approach. 29 The two senior authors (DEA and JPL) aim for GTR while recognizing that a small amount of residual tumor as a means of functional preservation is acceptable. Inclusion of various tumor sizes in this analysis highlights a potential difference in expectations between patients with small and large tumors; patients with larger tumors have a trend towards reporting improved PANQOL health and face scores, although these were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although these tumors are typically non-life-threatening, postoperative morbidity can be associated with injury to the facial nerve, cochlear nerve, cerebrospinal fluid leaks, and other wound complications. Permanent facial paralysis can occur in 3 to 5% of cases, and up to 22% of patients may experience cerebrospinal fluid leaks ( North et al, 2022 ). Fortunately, the surgical mortality rate is low, with less than 1% of cases resulting in death ( McClelland et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%